Young Grapevine Response and Root Colonisation fallowing Inoculation with Arbuscular Mycorrhizal Fungi - Meyer, A.H.; Valentine, A.J.; Botha, A.; Archer, E.; Louw, P.J.E. (South African Journal of Enology and Viticulture, 2017)
The host plant response following inoculation with commercially available arbuscular mycorrhizal (AM) fungi was determined in young grapevines under field conditions which would prevail on a typical farm. Measurements regarding growth improvement, nutrition and water relations were made in a field trial carried out on a commercial farm in the Stellenbosch region. Merlot noir grafted onto 101-14 Mgt and 110 Richter (110 R) in a Westleigh soil form and 99 Richter (99 R) in a Fernwood soil form was planted in December 1998. Vine roots were inoculated during planting with Biocult, Vaminoc and Glomus sp. 1054. Inoculation generally had little effect on xylem sap and leaf nutrient concentrations, water relations or growth responses. This was mainly ascribed to indigenous AM fungi, which seemed to have masked the effects of inoculation. A high soil P concentration was also implicated as a possible contributing factor to the general lack of grapevine response to AM inoculation.